Sensor/actuator fault tolerant sliding mode control for anti-lock braking in a quarter electric vehicle - Bambang L. Widjiantoro; Katherin Indriawati (Institute of Advanced Engineering and Science, 2020)
This paper proposes a scheme to improve regenerative ABS technology that already exists today by adding accommodation faults to the control system. The nominal control algorithm used is a sliding mode control so that system nonlinearities can be handled properly. The proposed method then is called sensor/actuator fault tolerant sliding mode control system. In designing the proposed control, there are two stages, namely estimation of faults, as well as the active mechanism for reconfiguring controls. Estimation of faults is done by using proportional-integral (PI) observers based on extended state space equation. Whereas the control signal reconfiguration is done actively by replacing measured output with their estimates and compensating for control signal using the actuator fault estimate. The simulation shows that the control system based on the proposed algorithm produces better dynamic performance than the sliding mode control (SMC) without fault tolerant feature. Furthermore, the system provides inherent characteristic for dealing with a minor fault in the hydraulic actuator.